Integrity levels of Chinese college students: An analysis of influencing factors - Li, Xiaohong; Zhao, Jin; Yan, Wenfan (Frontiers in Education, 2022)
College students' integrity is an important part of the growth of Chinese college students. The purpose of this survey study is to explore the integrity level of Chinese college students and to test the relationship between students’ integrity level and pre-determined influencing factors. The results of the 63 surveys collected from Student Affairs administrators indicated that they had high evaluation of the integrity level of Chinese college students, among which financial integrity was the highest, followed by employment integrity and academic integrity, and relationship integrity was the lowest. The pre-determined influencing factors of college students' integrity include the type of the colleges, the location of the colleges, system construction, carrier construction, environment construction and university management. System construction plays a significant role in students integrity level and has the most significant impact on students' academic integrity.